A Scientometric Review of Alexithymia: Mapping Thematic and Disciplinary Shifts in Half a Century of Research - Gaggero, Giulia; Bonassi, Andrea; Dellantonio, Sara; Pastore, Luigi; Aryadoust, Vahid; Esposito, Gianluca (Frontiers in Psychiatry, 2020)
Alexithymia is a personality trait consisting of altered emotional awareness. The history of this psychiatric construct begins in the early ‘70s when this term was introduced to define the peculiar psychological condition of some patients suffering from psychosomatic disorders. In half a century of research, the volume of scientific products focusing on alexithymia has exceeded 5,000. Such an expansive knowledge domain poses difficulty for those willing to understand how the scientific production on this condition is organized. Scientometrics embodies a solution to this issue, employing computational and visual analytic methods to uncover meaningful patterns within large bibliographical corpora. Specifically, these techniques offer an opportunity to investigate the trends and the evolution of the research on alexithymia. In this study, we applied co-citation techniques to investigate a corpus of 4,930 publications on Alexithymia ranging from 1980 to 2020 and their 100,251 references downloaded from the Web of Science. Through the CiteSpace software, we created interactive maps of co-cited documents, which were organized by clustering algorithms and explored by metrics of interest. Document co-citation analysis was performed to highlight pivotal publications on alexithymia and identify how major research areas developed through time. Journal co-citation analysis was conducted to find the main editorial venues focusing on alexithymia and disclose the disciplinary communities that are interested in this condition. Our analyses suggest that the construct of alexithymia experienced a gradual thematic and disciplinary shift. Although the first conceptualization of alexithymia came from psychoanalysis and psychosomatics, empirical research on this condition was pushed by the operationalisation of the construct formulated at the end of the ‘80s. Our results suggest that the Toronto Alexithymia Scale, the self-report instrument developed by the homonym research group, represented a watershed in the history of the construct. The same questionnaire encouraged both the entrance of new disciplines in the study of alexithymia (i.e. cognitive science and neuroscience) and an implicit redefinition of its conceptual nucleus. Overall, we discuss opportunities and limitations in the application of this bottom-up approach, which highlights trends in alexithymia research that were previously identified only through a qualitative, theory-driven approach.